ACTIVE LEISURE AND HEALTH PROMOTION: A SYSTEMATIC REVIEW OF THE LITERATURE (Fiep Bulletin - online, 2016)
Leisure plays an important role in life. Sowe cannot fail to point out that physical activityin leisure time becomes a factor of benefit to health and life of its practitioners. This study is an integrative review, which was carried out a search of scientific papers during the period from 2010 to 2014, on the basis of data from PUBMED, where selected five articles, whose what that met the inclusion criteria established.Observational studies was obtained relating leisure, health promotion and physical activity in different populations, children, adolescents, mothers, workers and seniors.Through analysis of these, we can ponder about the significant need to pursue an active lifestyle in the various stages of life, from childhood, adulthood and aging.
Keywords: leisure; health promotion; physical activity; health.